Educação do Campo na Amazônia: Um Olhar Freireano para Paráticas Educacionais - de Oliveira, Ivanilde Apoluceno; dos Santos, Tânia Regina Lobato (Revista Cocar, 2012)
Neste artigo faz-se recorte de uma pesquisa realizada nos anos de 2006 e 2007, com o objetivo de levantar experiências educacionais de educação no campo do Estado do Pará. O foco é para três práticas educacionais com crianças e quatro com jovens e adultos, de seis municípios do Estado do Pará: Bujarú, São Domingos do Capim, Alenquer, Breves, Santarém e Belterra, cujos projetos pedagógicos apresentam como base teórico-metodológica o pensamento educacional de Paulo Freire. Realizou-se levantamento bibliográfico e entrevistas semiestruturadas com 48 sujeitos, sendo 18 educandos, 10 gestores, 10 professores e 10 membros da comunidade. Na análise dos dados foram considerados três eixos temáticos: (1) gestão democrática; (2) a compreensão dos sujeitos sobre educação do campo; e (3) os indicadores pedagógicos, que marcam a diferença entre a prática pedagógica pesquisada e a tradicional e se tal prática está direcionada à educação do campo. Nortearam a análise as seguintes categorias: o diálogo, a participação democrática e a autonomia. Apresenta-se quem são os sujeitos do campo na Amazônia Paraense; as características das práticas educacionais pesquisadas e como suas ações pedagógicas expressam o ideário ético-político-pedagógico freireano. Palavras-Chave: Educação. Educação do Campo. Experiências Educacionais. Educação Popular Freireana. Country education in the Amazon: a look at Freireâ€™s educational experiences In this article one made a clipping of a research performed in the years of 2006 and 2007, with the objective of surveying educational experiences concerning country education in the state of Para. The focus is on 03 educational experien-ces with children and 04 experiences with young people and adults, from six municipalities of the state of Pará: Bujaru, São Domingos do Capim, Alenquer, Breves, Santarém and Belterra, whose pedagogical projects present as theoretical and methodological basis Paulo Freireâ€™s educational thought. One carried out a bibliographic survey as well as semi-structured interviews with 48 individuals, being 18 students, 10 educational managers, 10 teachers and 10 members from the country community. In the data analysis one considered three thematic axes: (1) democratic management; (2) the individualsâ€™ comprehension concerning country education; and (3) the peda-gogical indicators, which made the difference between the researched pedagogical practice and the traditional one and if this practice is directed to the country education. The following catego-ries guided the analysis: dialog, democratic par-ticipation and autonomy. One presents who the individuals from the Paraense Amazon country are; the characteristics of the researched educa-tional experiences and how these projects ex-press in their pedagogical practices the Freireâ€™s ethical-political-pedagogical ideas. Keywords: Education. Country Education. Educational Experiences. Freireâ€™s Popular Education.